Gut Microbiota and Non-Alcoholic Fatty Liver Disease: Current Pathogenic Paradigm and Therapeutic Aspect - Maimunah, Ummi; Soelistijo, Soebagijo Adi; Hadisuwarno, Wiharjo; Miftahussurur, Muhammad (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
Changes in the gut microbiota are essential factors that cause non-alcoholic fatty liver disease (NAFLD), obesity, and diabetes. Small intestine bacteria overgrowth is discovered in NAFLD patients. Disruptions in the gut-liver axis include environmental factors that induce microbiota dysbiosis and/or increased intestinal permeability that causes liver inflammation. The most recommended therapy for NAFLD patients is still limited to lifestyle changes. This review will describe the role of the gut microbiota in the pathogenesis and therapeutic intervention of NAFLD. Recent evidence reveals that the gut microbiota is one of the main factors in the pathogenesis and progression of NAFLD through several mechanisms, particularly dysbiosis. This significant role makes the gut microbiota a non-invasive biomarker for NAFLD examination and a more effective therapeutic target.